2010
DOI: 10.1146/annurev.soc.012809.102602
|View full text |Cite
|
Sign up to set email alerts
|

Conservative and Right-Wing Movements

Abstract: In recent years, the right has become a powerful force in many parts of the world. This review focuses primarily on the United States, with comparisons to rightist movements elsewhere. Our focus is movements, not political parties or intellectual trends. The article begins with terms and definitions and distinguishes conservative from right-wing movements. We then review changing theoretical orientations and the major findings on ideologies and characteristics of these movements. We also survey contextual fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
178
0
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(190 citation statements)
references
References 93 publications
0
178
0
12
Order By: Relevance
“…Within a social-cognition framework, a different literature has focussed on the ideological polarisation currently characterising many developed democracies [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72]. Most of this work has been carried out within English-speaking countries and is particularly suitable to the Australia setting [19,73,74].…”
Section: Analysis: Interpreting Our Results Within Common Narratives mentioning
confidence: 99%
“…Within a social-cognition framework, a different literature has focussed on the ideological polarisation currently characterising many developed democracies [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72]. Most of this work has been carried out within English-speaking countries and is particularly suitable to the Australia setting [19,73,74].…”
Section: Analysis: Interpreting Our Results Within Common Narratives mentioning
confidence: 99%
“…They are also manifested for some in the belief that growing secularism will lead to persecution of conservative Christians. In this scenario, a tyrannical state will remove religious liberties, civil liberties, and gun rights (Bivins 2008;Blee and Creasap 2010).…”
Section: Religion and Firearm Access Among Adolescentsmentioning
confidence: 99%
“…In the various studies that have analyzed online ER activity, certain differences can be observed among researchers in relation to their categorization of this activity and associated organizations (Blee & Creasap, 2010; see also Table 1). Burris, Smith, and Strahm (2000) proposed a set of eight primarily U.S.--centric categories in their analysis of a White supremacist website network; Holocaust Revisionists, Christian Identity Theology, Neo--Nazis, White Supremacists, Foreign (non--US) Nationalists, Racist Skinheads, Music, and Books/Merchandise.…”
Section: Er Categorizationmentioning
confidence: 99%